1988
DOI: 10.1002/eji.1830180613
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of extracellular Ca2+ and not recruitment from internal stores is essential for T lymphocyte proliferation

Abstract: Changes in free cytosolic calcium concentrations ([Ca2+]i) are thought to be important initiating events in the activation of T lymphocytes. Mitogen-induced increases in [Ca2+]i may result from net influx across the plasma membrane and/or release of Ca2+ from intracellular stores. In human T lymphocytes loaded with the fluorescent indicator indo-1, addition of phytohemagglutinin (PHA) or the anti-CD3 antibody UCHT-1 elicits a biphasic [Ca2+]i response. A major component of the initial transient peak was due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…1), but it is not possible to comment fully on the release of Ca 2 from endoplasmic reticulum stores. Initial reports on the rise in T cell Ca 2 after stimulation had suggested that the initial peak seen was mainly due to release of Ca 2 from intracellular stores [28]. Our own observations, and those of other groups [35][36][37], demonstrate that this store of Ca 2 contributes only a small fraction to the initial Ca 2 elevation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…1), but it is not possible to comment fully on the release of Ca 2 from endoplasmic reticulum stores. Initial reports on the rise in T cell Ca 2 after stimulation had suggested that the initial peak seen was mainly due to release of Ca 2 from intracellular stores [28]. Our own observations, and those of other groups [35][36][37], demonstrate that this store of Ca 2 contributes only a small fraction to the initial Ca 2 elevation.…”
Section: Discussionsupporting
confidence: 72%
“…The control cells gave the typical response observed by many groups [28][29][30], of an initial rapid increase in cytoplasmic calcium after a delay of 20-30 s from the addition of the stimulus. The rapid increase occurred over a period of about 30 s and was followed by a decline to an equilibrium calcium concentration, which was then sustained for the period of observation (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…This could, for instance, be the case in SCID patients carrying the ORAI1 mutation [13,14] [Ca 2+ ] i values at these time points, we cannot, however, imagine that these two time points do not reflect the general behavior over the 2 days. The initial high [Ca 2+ ] i , which is mostly due to Ca 2+ release is not sufficient to drive gene expression and cell proliferation [35]. This has been shown several times and recently most dramatically in some SCID patients with CRAC mutations [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In p56 lck expressing T cells, TCR stimulation is followed by an initial high transient Ca 2Ï© peak and a lower amplitude but sustained plateau phase (41,44,46). The initial rise of Ca 2Ï© is caused by the inositol trisphosphate-mediated release of Ca 2Ï© from the endoplasmatic reticulum (45) but is not sufficient for proliferation or IL-2 gene expression (41,71). Rather the prolonged elevation of intracellular Ca 2Ï© due to the Ca 2Ï© influx from extracellular sources is the critical component of the Ca 2Ï© signal (41,71).…”
Section: Figmentioning
confidence: 99%